Analysis of complications after operations with use of IVS tapes used for stress urinary incontinence treatment - Surkont, Grzegorz; Wlaźlak, Edyta; Stetkiewicz, Tomasz; Suzin, Jacek (Menopause Review/Przegląd Menopauzalny, 2006)
Aim of the study: The aim of the study was analysis of complications which occurred during and after IVS operations, which were performed in Clinic of Gynecology and Gynecologic Oncology, I Department of Gynecology and Obstetrics Medical University of Łódź. Material and methods: Prospective analysis was done among first 110 operations which were performed by 3 gynecologists in women with SUI 2nd and 3rd degree, in whom there was not detected paravaginal defect nor OAB. Diagnosis was made on the grounds of the results of urogynecologic and urodynamic exam Results: Among complications, which occured in 19 patients (17.27%) there were: bleeding to Retzius space, foreign body like reactions (erosions), infections of lower urinary tract, post void residual, OAB de novo . We had no case of bladder perforation. This can be the result of detailed hydrodessection, plastic end of IVS needle and gentle introducing the needle. High percentage of erosions may be the result of learning curve as well of the properties of the tape. Conclusions: 1. Operation with use of IVS tape has low risk of complications. 2. Detailed hydrodessection, plastic end of IVS needle and gentle introducing the needle lowers risk of bladder perforation. 3. Tape insertion without cough test minimizes the risk of overcorrection and post-void urine residual.